2019
DOI: 10.4103/jfmpc.jfmpc_832_19
|View full text |Cite
|
Sign up to set email alerts
|

Profile of acute poisoning cases and their outcome in a teaching hospital of north India

Abstract: Objectives:Aim of this study was to characterize acute poisoning and snakebite cases and their outcome in the Emergency Department (ED).Methods:This was a prospective study done in the ED of a tertiary healthcare center. Study included 184 patients of acute poisoning and 16 cases of snakebite. Data regarding demographics, type, time, and mode of poisoning, lag time in reaching the hospital, initiation of treatment, first aid, in-hospital treatment, and comorbid illness were obtained. Data regarding requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
1
13
2
Order By: Relevance
“…The finding contradicts the studies conducted in Turkey, Ethiopia, and Eastern Nepal which reported no significant association between mode of poisoning and poor treatment outcome of acute poisoning. 4,7,12,13,39 In the current study, the odds of having poor treatment outcome in participants who were poisoned by drugs was 2.13 time more likely than non-drugs poisoning. Improving rational use of drugs and counseling the patients in their drugs would decrease the number of severe acute poisoning cases.…”
Section: Poisoning (N) Antidote(n)mentioning
confidence: 49%
See 2 more Smart Citations
“…The finding contradicts the studies conducted in Turkey, Ethiopia, and Eastern Nepal which reported no significant association between mode of poisoning and poor treatment outcome of acute poisoning. 4,7,12,13,39 In the current study, the odds of having poor treatment outcome in participants who were poisoned by drugs was 2.13 time more likely than non-drugs poisoning. Improving rational use of drugs and counseling the patients in their drugs would decrease the number of severe acute poisoning cases.…”
Section: Poisoning (N) Antidote(n)mentioning
confidence: 49%
“…A data abstraction format adapted from different literature, 4,7,10,12,13 was used to record the necessary information from patients' medical records. The data abstraction format was prepared in English language and included variables like sex of patients, age of patients, residence, route of poisoning, type of poisoning, clinical presentations, the status of patients when coming to the hospital, reason of patients for taking the poison, time of arrival to the emergency of the hospital, source of poisoning agents, length of hospital stay, treatment given for the acute poisoning, and treatment outcome.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Data abstraction was adapted from previous studies (Desalew et al, 2011 ; Mathew et al, 2019 ; Tefera & Teferi, 2020 ; Wakushie & Daba, 2016 ; Woyessa & Palanichamy, 2020 ). The poison cases were diagnosed based on the history given by the patients/family members, clinical presentation, and laboratory investigations.…”
Section: Methodsmentioning
confidence: 99%
“…The late-onset symptom is peripheral neuropathy. [ 3 ] Intermediate syndrome (IMS) usually occurs after 2-4 days after oral exposure of OP poisoning. It is seen in around 20% of the cases of OP poisoning.…”
Section: Introductionmentioning
confidence: 99%